Fe-doped V2O5 layered nanowire cathode material with high lithium storage performance. (4th June 2023) - Peng, Xiaoxiao; Zou, Zhengguang; Ling, Wenqin; Liang, Fangan; Geng, Jing; Zhang, Shuchao; Zhong, Shenglin
Abstract: As a lithium-ion battery cathode material with high theoretical capacity, the application of V2 O5 is limited by its unstable structure and low intrinsic conductivity. In this paper, we report a Fe doped V2 O5 nanowire with a layered structure of 200–300 nm diameter prepared by electrostatic spinning technique. The 3Fe-V2 O5 electrode exhibited a superb capacity of 436.9 mAh g −1 in the first cycle when tested in the voltage range of 2.0–4.0 V at current density of 100 mA g –1, far exceeding its theoretical capacity (294 mAh g −1 ), and the high capacity of 312 mAh g −1 was still maintained after 50 cycles. The superb performance is mainly attributed to its unique layered nanowire structure and the enhanced electrical conductivity as well as optimized structure brought by Fe-doping. This work made the homogeneous doping and nanosizing of the material easily achieved through electrostatic spinning technology, leading to an increase in the initial capacity of the V2 O5 cathode material and the cycling stability compared to the pure V2 O5, which is an extremely meaningful exploration.